Autonomic nervous system in arterial hypertension and heart failure: current understanding of its pathophysiologic role and innovative treatment approaches - A. O. Konradi (Российский кардиологический журнал)
This review presents the modern understanding of the role of autonomic nervous system dysfunction in the development of arterial hypertension and heart failure. It also discusses the innovative treatment approaches which target various components of autonomic nervous system in order to treat cardiovascular disease.